2006
DOI: 10.1099/vir.0.81660-0
|View full text |Cite
|
Sign up to set email alerts
|

Protection of mice against Human respiratory syncytial virus by wild-type and aglycosyl mouse–human chimaeric IgG antibodies to subgroup-conserved epitopes on the G glycoprotein

Abstract: Monoclonal antibodies (mAbs) to conserved epitopes on the G glycoprotein of human respiratory syncytial virus (HRSV) subgroup A fail to neutralize the virus in cell culture in the absence of complement, but are protective in rodent models of infection. They may have potential as prophylactic agents in human infants. In order to investigate the role of Fc-dependent pathways in protection by one such antibody, 1C2, the V H and V L genes were isolated by RT-PCR and assembled with human k light-chain and human c1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Two days after mAb 131-2G treatment, the viral load in mice treated with intact mAb was significantly (P,0.048) reduced compared with lung titres in F(ab9) 2 -treated mice which showed no significant reduction compared with nIgtreated mice. The ability of this non-neutralizing antibody to prevent virus replication in vivo is consistent with earlier observations and reports using other non-neutralizing RSV G protein antibodies (Corbeil et al, 1996;PlotnickyGilquin et al, 1999;Mekseepralard et al, 2006). The results suggest that mAb 131-2G may mediate virus clearance through an ADCC mechanism.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Two days after mAb 131-2G treatment, the viral load in mice treated with intact mAb was significantly (P,0.048) reduced compared with lung titres in F(ab9) 2 -treated mice which showed no significant reduction compared with nIgtreated mice. The ability of this non-neutralizing antibody to prevent virus replication in vivo is consistent with earlier observations and reports using other non-neutralizing RSV G protein antibodies (Corbeil et al, 1996;PlotnickyGilquin et al, 1999;Mekseepralard et al, 2006). The results suggest that mAb 131-2G may mediate virus clearance through an ADCC mechanism.…”
supporting
confidence: 81%
“…In these previous studies, treatment with the same mAb in complement-deficient mice or treatment with mAb F(ab9) 2 fragments did not confer complete protection, suggesting that protection by the intact mAb involved both Fc-dependent pathways and the complement system (Corbeil et al, 1996). Other studies investigating a different subgroup A-specific anti-RSV G mAb (1C2) that recognized a similar region on the G protein, and a related mouse-human chimeric mAb (c1 1C2), showed a level of protection against RSV infection when these antibodies were administered prophylactically to BALB/c mice (Mekseepralard et al 2006). In these studies, virus replication was minimally inhibited in mice treated with an aglycosyl chimeric mAb defective in complement activation, FccR binding and, therefore, ADCC activation, leading to the conclusion that protection from RSV infection was mediated by both Fc-dependent and Fc-independent mechanisms (Mekseepralard et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Murine Abs to the central conserved region of the G protein have shown efficacy in prophylactic mouse (29) and cotton rat models (30). A recent report showed that such a murine mAb delivered postinfection decreased both viral replication and the associated pulmonary inflammatory response (31).…”
mentioning
confidence: 99%